Braced - Gerber, Alyson (Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
When twelve-year-old Rachel learns that her scoliosis has worsened and she will need to wear a back brace to keep her spine straight, she is devastated; afraid that she will not be able to play soccer, and terrified that she will not be able to hide her condition from her friends and classmates--but her mother is determined to spare her the spinal fusion surgery that she herself had as a teenager.